Odpowiedź :
Zad 2
a) 4x - 7 = 2x + 9
2x = 16 /:2
x = 8
b) 3 - 8x = 18- 3x
- 15 = 5x / :5
x = -3
c) 2 - x = 12 + 7x
-10 = 8x / :8
x = -[tex]\frac{10}{8}[/tex]
x = - [tex]\frac{5}{4}[/tex]
d) 3x + 5x -6 = 6x + 2
2x = 8 /:2
x = 4
e) 5 - 9x + 6 = 2x + 14 - x
- 3 = 10x /:10
x = - [tex]\frac{3}{10\\}[/tex]
Zad 3
a) x(3x + 2)=3(x²- 4)
3x² + 2x = 3x² - 12
2 x = -12
x = -6
b) 6(1+2x²)=3(x²-4)
6 + 12x² = 3x² - 12
9x² = - 18/ :9
x² = -2
równanie sprzeczne ponieważ x podniesiony do kwadratu nie może dac liczby ujemnej
c) 3x(x-5)=(3x+2)(x-1)
3x² - 15x = 3x² -3x +2x - 2
- 15x = -3x + 2x - 2
-15x = -x -2
-14x = -2
x = -[tex]\frac{1}{7}[/tex]